Hessen, Deutschland: LOEWE Schwerpunkt „Prähistorische Konfliktforschung“ – Projektteil: Befestigte Höhensiedlungen zwischen Taunus und Vogelsberg - Neumann, Daniel; Krause, Rüdiger; Hansen, Svend (e-Forschungsberichte des DAI, 2023)
Within the research focus “Prehistoric Conflict Research” the Romano- Germanic Commission is conducting research on Bronze Age hillforts between Taunus and Vogelsberg. The first year’s work was devoted to the identification and evaluation of the Bronze Age occupation of already known hilltop sites. This objective was on the one hand achieved through the evaluation of existing archaeological data, which had not been analysed in detail before. On the other hand the approach was complemented by intensive surveys which aim to identify currently unknown sites through remote sensing and geophysical prospections.